A Critique of the Epistemic Function of Religious Beliefs in the Light of the Cognitive Science of Religion (in Polish) - Szocik, Konrad (Diametros, 2016)
Religious beliefs and religion are usually interpreted in terms of their social functionality and motivating social cooperation, as well as in terms of their alleged truthfulness. Here I suggest interpreting religious beliefs and religion with regard to their psychological function. I claim that their pro-social function is an accidental property, reducible to some mechanisms of tribal psychology, rather than a feature of religion itself. I emphasize that the epistemic function is not the main function of religious beliefs and religion. These beliefs are in some sense immune to critique due to their merely psychological function. Throughout my paper I refer to the cognitive science of religion.